Optimization Of Digital Leadership To Strengthen Order Maintenance Performance So That Increase Public Trust - Purba, David Pratama (Advances In Social Humanities Research, 2024)
This study investigates the enhancement of digital leadership to bolster order maintenance performance and elevate public trust in the Central Jakarta Metro Police following Law Number 2 of 2002 regarding the National Police. Public trust is crucial for effective order maintenance, particularly in the digital disruption era. The study addresses three key aspects: (1) How digital leadership inspires others, (2) How technology is utilized in digital leadership, and (3) How collaboration is fostered through digital leadership. By fostering digital leadership that inspires others, leverages technology, and promotes collaboration, the aim is to ensure stable order maintenance performance. The theoretical framework encompasses digital leadership, inspiration theory, technology utilization, collaboration, digitalization, communication, innovation, and trust concepts. Employing a descriptive qualitative approach, data collection techniques include observation, interviews, questionnaires, and document review. Analysis techniques such as SWOT, EFAS, IFAS, AHP, SFAS, and risk management are employed. Findings reveal suboptimal implementation of digital leadership at the Central Jakarta Metro Police. Factors influencing optimization include the inspiration of others, technology usage, and collaboration. Recommendations include strategic steps in digital leadership, spanning short-term, medium-term, and long-term measures to bolster public trust.